Memahami Preferensi Platform Media Sosial pada UMKM Indonesia: Perspektif Technology Acceptance Model terhadap Strategi Promosi Digital berbasis Sektor Usaha - Armawan, Ivan; Indra Saputra Alamsyah, Andi; Narendra Muvano, Nandha; Ayu Lestariani, Made; Ananda Pratama, Irfan (LP3M, Universitas Muhammadiyah Kendari, 2026)
This research was conducted in Balikpapan City, focusing on three MSMEs operating in the culinary sector (Kampoeng Timoer), handicraft sector (D'Hands Project), and fashion sector (Jesthink). Data collection techniques included direct observation, structured interviews, and documentation of social media content. Subsequently, the collected data were analyzed using thematic analysis techniques assisted by NVivo 12 software. This study addresses a research gap concerning the absence of experience-based mapping of social media channel preferences among Micro, Small, and Medium Enterprises (MSMEs) in the local Indonesian context, employing a descriptive qualitative approach strengthened by the Technology Acceptance Model (TAM) as a novelty framework. The findings not only map the dominance of Instagram and WhatsApp Business as the two primary platforms but also reveal that preferences for these two platforms are driven by perceived ease of access, communication effectiveness, and alignment with product characteristics. The novelty of the findings lies in identifying differences in content strategies across business sectors (culinary, fashion, handicraft) that have been overlooked by previous studies. This study also identifies several significant challenges faced by MSME actors, including limited digital literacy, time constraints in consistently managing content, and the absence of data-driven strategic promotion planning. The novel contribution of this research is the formulation of contextual and sector-differentiated mentoring recommendations for MSMEs.